CROSS-CULTURAL ADAPTATION OF CHINESE STUDENTS: PROBLEMS AND SOLUTIONS - Songsirisak, Prommin (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2018)
บทคัดย่อ เนื่องด้วยจำนวนนักศึกษาจีนที่เพิ่มขึ้นอย่างรวดเร็วในมหาวิทยาลัยไทย ส่งผลให้เกิดความกังวลเรื่องสวัสดิการและความสามารถในการปรับตัวให้เข้ากับวัฒนธรรมไทยและการดำเนินชีวิตในรั้วมหาวิทยาลัย ความคิดเห็นของนักศึกษาจีนในช่วงที่ผ่านมาได้แสดงให้เห็นว่า มีนักศึกษาจีนเพียงบางส่วนที่สามารถปรับตัวได้เป็นอย่างดี ในขณะที่คนส่วนใหญ่ประสบกับปัญหาการปรับตัวทางวัฒนธรรมที่ไม่คุ้นเคยอันเนื่องมาจากการขาดกลยุทธ์ในการจัดการกับประสบการณ์ทางวัฒนธรรมในสภาวะใหม่ อีกทั้งยังมีความรู้ทางด้านวัฒนธรรมไทยที่ไม่เพียงพอ และขาดความสามารถในการสื่อสารข้ามวัฒนธรรม ดังนั้น การศึกษาวิจัยในครั้งนี้ จึงมุ่งศึกษาปัญหาการปรับตัวข้ามวัฒนธรรมและค้นหากลยุทธ์และแนวทางการแก้ไขปัญหาสำหรับนักศึกษาจีนก่อนเดินทางเข้ามาศึกษา ณ ประเทศไทย แบบสอบถามปลายเปิดถูกใช้เป็นเครื่องมือในการเก็บรวบรวมข้อมูล วิจัยจากนักศึกษาจีน จำนวน 30 คน ที่กำลังศึกษาได้ระยะเวลา 3 เดือน ณ มหาวิทยาลัยไทยและข้อมูลถูกนำไปวิเคราะห์โดยวิธีการวิเคราะห์แบบ open and axial coding techniques (Strauss and Corbin, 1990) ผลการวิจัยพบว่า ปัญหาหลักที่สำคัญของการปรับตัวทางวัฒนธรรม คือ ปัญหาด้านการใช้ภาษาอังกฤษและภาษาไทย ขาดกลยุทธ์ในการสื่อสารข้ามวัฒนธรรมกับคนไทย ไม่คุ้นเคยกับมารยาทไทย อาหารไทย พฤติกรรมทางสังคมที่เหมาะสม และวัฒนธรรมการเรียนการสอนของไทยสำหรับด้านกลยุทธ์และแนวทางการแก้ไขปัญหานั้น ผลงานวิจัยได้เสนอแนะ 3 แนวทางหลัก คือ นักศึกษาจีนควรเพิ่มพูนความรู้ทางด้านภาษาและวัฒนธรรมไทย เพิ่มทักษะและความสามารถที่ดีในการสื่อสารข้ามวัฒนธรรมสำหรับสื่อสารกับคนไทย และมหาวิทยาลัยในจีนควรจัดให้มีการอบรมปฐมนิเทศก่อนเดินทางมาศึกษา ณ ประเทศไทยเพื่อให้เข้าใจถึงพฤติกรรมทางวัฒนธรรมไทยที่เหมาะสม มารยาทไทย และลักษณะการเรียนในมหาวิทยาลัยไทย คำสำคัญ : การเรียนในมหาวิทยาลัยต่างประเทศ การปรับตัวข้ามวัฒนธรรม การสื่อสารข้ามวัฒนธรรม ABSTRACT 1Faculty of Humanities, Chiang Rai Rajabhat University, Thailand With the rapid increase of Chinese students studying at Thai universities, there is a growing concern for their welfare and ability to adapt to life at Thai universities and function successfully in Thai culture. Comments from past students show that a few can adapt, but most encounter problems such as prolong culture shock due to lack of strategies for dealing with new cultural experiences, inadequate knowledge of Thai culture and poor intercultural communication ability. Therefore, this study was initiated to investigate cross-cultural adaptation problems and find solutions and strategies for Chinese students to consider before coming to study in Thailand. Data were collected through an open-response questionnaire with thirty new comer Chinese students who had been studying English at a Thai university for three months. The open and axial coding techniques (Strauss and Corbin, 1990) were used for data analysis. The findings revealed that the most significant problems for cultural adaptation were including language barriers in both English and Thai, having no strategies for inter-cultural communication with Thai people, not being familiar with Thai etiquette and food, appropriate social behavior and Thai classroom culture. As far as solutions and strategies, the research recommends three main areas including increasing the study of Thai language and culture, having better competence in inter-cultural communication strategies for talking with Thai people, and providing more detail orientation training before coming to Thailand in order to understand proper Thai cultural behavior, etiquette and Thai university study habits. Keywords: Foreign University Study, Cross-Cultural Adaptation, Inter-Cultural Communication